2019
DOI: 10.3897/oneeco.4.e37669
|View full text |Cite
|
Sign up to set email alerts
|

Changes in land cover and grassland area over the past 120 years in a rapidly urbanised area in Japan

Abstract: In wet temperate regions, human activity has played an important role in shaping the size and distribution of grasslands. We examined change in land cover type and grassland area in a 9.2 × 22.3 km area of northern Chiba Prefecture, based on historical maps and documents for four time periods (1880s, 1950s, 1980s and 2000s). In the 1880s, conifer forests occupied the largest area (43.1%) amongst land cover types and grasslands accounted for 4.2% of the total area. However, literature available from the 1880s s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
2
17
0
1
Order By: Relevance
“…Cousins (2009) found that time-delayed response is detected in regions where contemporary landscapes retain >10% of traditional habitats. As our study region maintains only 2.8% of remnant grasslands of those in 1880s (Noda et al, 2019), delayed responses may not have been observed.…”
Section: Landscape Structure and Its Consequences On Species Composmentioning
confidence: 84%
See 1 more Smart Citation
“…Cousins (2009) found that time-delayed response is detected in regions where contemporary landscapes retain >10% of traditional habitats. As our study region maintains only 2.8% of remnant grasslands of those in 1880s (Noda et al, 2019), delayed responses may not have been observed.…”
Section: Landscape Structure and Its Consequences On Species Composmentioning
confidence: 84%
“…Grasslands in this region had historically been maintained as a pasture for warhorses, but since the middle of 19th century began to be changed to coppice woodlands dominated mainly by pine trees (Miyamoto & Yokohari, 2010). Due to frequent tree cutting, the coppice in these landscapes was generally sparse with short trees, allowing grassland-like vegetation to persist until the 1960s (Koyanagi, Kusumoto, Yamamoto, & Takeuchi, 2012b;Noda, Kondoh, & Nishihiro, 2019). After this, suburban development took place and earthmoving accompanied by topsoil removal and ground leveling was carried out in this region.…”
Section: Study Sitesmentioning
confidence: 99%
“…The pattern of replacement of forests and grasslands to residential areas is typical at the scale of the prefectures surrounding the study site [27,31,61]. Generally, in Japan's metropolitan areas, urban sprawl aggravated the farming environment.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies point out that biodiversity richness was affected by decades of habitat connectivity, particularly in human-maintained grasslands, which are symbolic human-modified landscapes [15,[56][57][58][59][60]. It is necessary to prioritize certain conservation goals by investigating historical land cover transitions and maintaining continuity, including in the context of urban nature [6,61]. Therefore, the urban green space patches that replaced grassland-like environments that were under the control of rural communities are important as a remnant for human-modified landscapes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation